Iranian National Security: Repercussions of Negotiations with the Great Powers - Alaa , Assist. Lecturer Nashwan (The International and Political Journal, 2023)
Negotiations constitute the first step on which countries rely to settle their differences peacefully, especially as they realize that the alternative to negotiations will have exorbitant and disastrous consequences. There is no doubt that the negotiation process is a series of activities that need a comprehensive program to define the goals and means of achieving the required results, anticipating what the negotiation process mechanism will interpret, which is known as the negotiation strategy. The Iranian negotiations with the great powers do not deviate from this framework, as each party seeks to implement several strategies to achieve the greatest possible gains. These negotiations received wide attention because of their significant impact on security stability in the region in general and the Arabian Gulf region in particular. The Western and Iranian negotiating parties regarding the Iranian nuclear project used both strategies of common interest and conflict at the same time. While the Iranians seek to achieve the goal of producing nuclear energy with minimal losses, the Western powers seek to stop the Iranian nuclear program and subject Iranian policy to their will.